Hispid pocket mice in tallgrass prairie: abundance, seasonal activity, habitat association, and individual attributes - Kaufman, Glennis A.; Kaufman, Dawn M.; Kaufman, Donald W. (My University, 2013)
Hispid pocket mice (Chaetodipus hispidus) are found from the grasslands of the Great Plains to the deserts of the southwestern United States, but the natural history and ecology of this species have not been described in native tallgrass prairie at the eastern edge of its range. We initiated an ongoing long-term study of small mammals on Konza Prairie Biological Station, Kansas (a Long-Term Ecological Research [LTER] site), in autumn 1981. Our sampling scheme for 14 LTER sites was a 20-station trapline; small mammals were sampled in autumn and spring for 30 years and in summer for a shorter period. We combined data for these sites with those from shorter studies on Konza Prairie that used traplines and trapping grids. We recorded only 96 hispid pocket mice over the 30 years of study (>300,000 trap-nights overall). Pocket mice were more likely to be captured in autumn and summer than in spring. The earliest annual capture was on 20 March and the latest on 7 December; males emerged from torpor in spring before females, whereas females entered torpor later in autumn. Precipitation (January–September) had a tight limiting effect on maximal number of individuals that were present in autumn. Pocket mice were more common on slope prairie than on upland or lowland prairie, but burning and grazing had no effect. Their spatiotemporal distribution showed a slightly “anti-nested” pattern with only weakly preferred sites and no focal years that might indicate favorable conditions. Collectively, our data suggested the presence of 3 age classes when individual body masses (no differences between males and females) were plotted against capture date. Finally, our study illustrates the importance of long-term data sets, especially in the study of uncommon to rare species.
Keywords: Hispid pocket mice; Tallgrass prairie; Konza Prairie Biological Station